2009
DOI: 10.1086/599764
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity Cost Neglect

Abstract: To properly consider the opportunity costs of a purchase, consumers must actively generate the alternatives that it would displace. The current research suggests that consumers often fail to do so. Even under conditions promoting cognitive effort, various cues to consider opportunity costs reduce purchase rates and increase the choice share of more affordable options. Sensitivity to such cues varies with chronic dispositional differences in spending attitudes. We discuss the implications of these results for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
240
11
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(268 citation statements)
references
References 29 publications
15
240
11
2
Order By: Relevance
“…Our conclusions are related to work on consideration of opportunity costs (Bartels and Urminsky 2015;Frederick et al 2009;Spiller 2011) and earmarking (Cheema and Soman 2011;Webb and Spiller 2014). These research streams examine how potential uses of money-spontaneously generated or provided-influence spending decisions.…”
Section: Discussionmentioning
confidence: 83%
“…Our conclusions are related to work on consideration of opportunity costs (Bartels and Urminsky 2015;Frederick et al 2009;Spiller 2011) and earmarking (Cheema and Soman 2011;Webb and Spiller 2014). These research streams examine how potential uses of money-spontaneously generated or provided-influence spending decisions.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, opportunity cost information was more likely to be taken into account in decision-making when it was explicitly provided than not. Frederick et al (2009) recently documented this phenomenon in purchase decision-making. For example, in one study, half of the participants chose between the options "buy this entertainment video" and "not buy this entertainment video" (control condition); the other half of the participants chose between "buy this entertainment video" and "keep the money for other purchases" (opportunity cost salient condition).…”
Section: Opportunity Cost Neglectmentioning
confidence: 91%
“…Rationally speaking, people should consider opportunity cost (i.e., the alternative returns one has to give up) in their decisions to maximize the returns. Yet, empirical evidence has documented that people rarely take opportunity cost into consideration in decision-making, if information about opportunity cost is not explicitly presented (Northcraft and Neale, 1986;Frederick et al, 2009;Shavit et al, 2011). For instance, Northcraft and Neale (1986) found that participants were less likely to consider opportunity cost when opportunity cost information was not mentioned; however, participants altered their decisions to be congruent with the traditional cost/benefit analysis paradigm proposed by economists when they were presented with explicit opportunity cost information.…”
Section: Opportunity Cost Neglectmentioning
confidence: 99%
See 2 more Smart Citations